2006
DOI: 10.1177/0165025406062128
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the transition to adulthood among Chinese and American emerging adults

Abstract: This study explored cultural differences in the criteria young people have for becoming an adult. Specifically, the study sought (a) to compare Chinese and American responses concerning whether they believe they have reached adulthood; (b) to examine whether adulthood criteria could fit a common statistical model for both cultures; and (c) after estimating this model, to compare the importance of adulthood criteria for Chinese and Americans. Results indicated that Chinese students considered themselves to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
145
4
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(164 citation statements)
references
References 22 publications
13
145
4
2
Order By: Relevance
“…Similarly, the items on the Role Transitions subscale were drawn from the sociological literature, which has long used a series of specific role transitions as the defining criteria for the transition to adulthood (Goldscheider & Goldscheider, 1999;Hogan & Astone, 1986). The analysis of internal consistency pointed out that alpha levels of these subscales were considerably better in our sample than in previous studies, where internal consistency has always been moderate or low (e.g., Arnett, 2003;Sirsch et al, 2009) (Badger et al, 2006;Mayseless & Scharf, 2003). Therefore, Arnett's conceptual model shows high face validity, whereas statistical evidence for this model might lack (e.g., Barker & Galambos, 2005).…”
Section: Methodsmentioning
confidence: 71%
See 3 more Smart Citations
“…Similarly, the items on the Role Transitions subscale were drawn from the sociological literature, which has long used a series of specific role transitions as the defining criteria for the transition to adulthood (Goldscheider & Goldscheider, 1999;Hogan & Astone, 1986). The analysis of internal consistency pointed out that alpha levels of these subscales were considerably better in our sample than in previous studies, where internal consistency has always been moderate or low (e.g., Arnett, 2003;Sirsch et al, 2009) (Badger et al, 2006;Mayseless & Scharf, 2003). Therefore, Arnett's conceptual model shows high face validity, whereas statistical evidence for this model might lack (e.g., Barker & Galambos, 2005).…”
Section: Methodsmentioning
confidence: 71%
“…In this sense, results from the groups of individuals from Italy reflect how much the goal of forming a family in the future is crucial for their adult lives. Different cultural perceptions of what are the important criteria for reaching adulthood have been previously explained by individualistic vs. collectivistic societies' values (e.g., Badger, Nelson, & Barry, 2006;Piumatti, Pipitone, Di Vita, Latina, & Rabaglietti, 2013). Although the shared markers emphasize individualism, at the same time, they include collectivistic views.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, attempts to replicate Arnett's conceptually derived domains using factor analyses failed both at Time 1 and Time 2, with poor overall fit and very low factor loadings, particularly for the independence and interdependence factors. Other studies also failed to replicate these factors (Badger, Nelson, & Barry, 2006;Mayseless & Scharf, 2003). Hence, it can be concluded that although Arnett's conceptual model shows high face validity (e.g., Barker & Galambos, 2005), statistical evidence for this model is lacking.…”
Section: Methodsmentioning
confidence: 99%